Sistem Informasi Geografis Berbasis Web Untuk PenyebaranFasilitas Umum Di Kabupaten Klaten - Faisal, Abul Nizam; , Nurgiyatna, S.T., M.Sc., Ph.D (2016)
The existence of public facilities in the City of Klaten spread enough evenly in various places, but until now there is no description about the geographical position of the existence public facilities. therefore needed an information system that can provide presence information of the location in public facilities in Klaten. The purpose of this research is to develop their webbased geographic information system for the dissemination of public facilities in the Klaten. The methodology used of develop this system is using waterfall method. For displaying a map using the API of Google Maps, php framework using Code Igniter, CSS erformed by administrator and questionnaire testing can be conclude that the system is running properly. The results of this research is a web-based geographic information system for the dissemination of public facilities in Klaten that can show the location of public facilities in Klaten and related information from the public facilities, so as to facilitate the delivery of information the locations of public facilities to the public. Keywords: Geographic information system, maps, public facilities, codeigniter